Integrating driver behavior into last-mile delivery routing: Combining machine learning and optimization in a hybrid decision support framework - Dieter, Peter; Caron, Matthew; Schryen, Guido (European Journal of Operational Research (EJOR))

Architectural Management of OTF Computing Markets - Gottschalk, Sebastian; Vorbohle, Christian; Kundisch, Dennis; Engels, Gregor; Wünderlich, Nacy V. (On-The-Fly Computing -- Individualized IT-services in dynamic markets)

The Market for Services: Incentives, Algorithms, Implementation - Haake, Claus-Jochen; Hehenkamp, Burkhard; Polevoy, Gleb (On-The-Fly Computing -- Individualized IT-services in dynamic markets)

Empirical Analysis in Markets for OTF Services - Elrich, Alina; Kaimann, Daniel; Fahr, René; Kundisch, Dennis; Mir Djawadi, Behnud; Müller, Michelle; Poniatowski, Martin; Schäfers, Sabrina; Frick, Bernd (On-The-Fly Computing -- Individualized IT-services in dynamic markets)

Zusatzkosten der Besteuerung – Eine Analyse des steuerlichen Verwaltungsaufwands und der subjektiv wahrgenommenen Steuerbelastung - Fochmann, Martin; Heinemann-Heile, Vanessa; Huber, Hans-Peter; Maiterth, Ralf; Sureth-Sloane, Caren (Steuer und Wirtschaft)

Anticipatory Assignment of Passengers to Meeting Points for Taxi-Ridesharing - Dieter, Peter; Stumpe, Miriam; Ulmer, Marlin Wolf; Schryen, Guido (Transportation Research Part D)

Gelingensbedingungen gestaltungsorientierter Schulentwicklung - Schwabl, Franziska; Daniel-Söltenfuß, Desiree (Organisation zwischen Theorie und Praxis)

„Allowing the Economy to Breathe Even During the Crisis“ – Interview with Tax Expert Caren Sureth-Sloane - Unterstell, Rembert (german research – Magazine of the Deutsche Forschungsgemeinschaft)

#DIGITALENTS - Digital Talents Programm geht in die zweite Runde - Kundisch, Dennis

Digitale Transformation im Theater – Mittels Besucherforschung und Entscheidungsunterstützung zur besseren Angebotsgestaltung - Kempkes, J. P.; Kreuzhage, K.; Kundisch, Dennis; Seutter, Janina; Weskamp, Christoph (Kultur Management Network Magazin)

Life-cycle health effects of compulsory schooling - Schmitz, Hendrik; Tawiah, Beatrice Baaba
We study the effect of education on health (hospital stays, number of diagnosed conditions, self-rated poor health, and obesity) over the life-cycle in Germany, using compulsory schooling reforms as a source of exogenous variation. Our results suggest a positive correlation of health and education which increases over the life-cycle. We do not, however, find any positive local average treatment effects of an additional year of schooling on health or health care utilization for individuals up to age 79. An exception is obesity, where positive effects of schooling start to be visible around age 60 and become very large in age group 75-79. The results in age group 75-79 need to be interpreted with caution, however, due to small sample size and possible problems of attrition.
Keywords: Education; health; life-cycle effects; compulsory schooling

Housing Situations and Local COVID-19 Infection Dynamics – A Case Study With Small-Area Data - Freise, Diana; Schiele, Valentin; Schmitz, Hendrik
Keywords: General Earth and Planetary Sciences; General Environmental Science

The effect of compulsory schooling on vaccination against COVID and Influenza - Monsees, Daniel; Schmitz, Hendrik
We study the effect of education on vaccination against COVID-19 and influenza in Germany and Europe. Our identification strategy makes use of changes in compulsory schooling laws and allows to estimate local average treatment effects for individuals between 59 and 91 years of age. We find no significant effect of an additional year of schooling on vaccination status in Germany. Pooling data from Europe, we conclude that schooling increases the likelihood to vaccinate against COVID by an economically negligible effect of one percentage point (zero for influenza). However, we find indications that additional schooling increases fear of side effects from COVID vaccination.
Keywords: COVID; influenza; vaccination; education; compulsory schooling

Unboxing video effectiveness – Does speech matter? - Garnefeld, I.; Böhm, Eva; Hanf, L.; Helm, S. (2023 AMA Summer Academic Conference, San Francisco, CA)

The dark and bright side of online reviews in manufacturer online shops - Kessing, K.; Garnefeld, I.; Böhm, Eva (EMAC Annual Conference, Odense, Denmark)

Stimulating engagement with unboxing videos – Does speech matter? - Hanf, L.; Garnefeld, I.; Böhm, Eva; Helm, S. (EMAC Annual Conference, Odense, Denmark)

Bring me my Meal on your Wheel - An Empirical Analysis of the Impact of Food Delivery Platforms on Local Restaurant Employment - Müller, Michelle; Neumann, Jürgen (Proceedings of the 55th Hawaii International Conference on System Sciences (HICSS))

Digital technology usage as a driver of servitization paths in manufacturing industries - Harrmann, Lisa Katharina; Eggert, Andreas; Böhm, Eva (European Journal of Marketing)
Purpose This study aims to conceptually propose and empirically validate a path perspective on the servitization process of manufacturing firms. It identifies a customer and an outcome path to servitization, sheds light on the pivotal role of digital technology usage for both value-creating paths and explores their financial and relational performance outcomes. Design/methodology/approach The authors use a mixed-method approach, combining a qualitative study with a cross-sectional survey in the USA, the UK and Germany. Findings Manufacturing firms choose between two generic paths to servitization, a customer and an outcome path. Digital technology usage is equally important for both value-creating paths. Progress on the outcome path has a positive effect on firms’ financial performance, whereas the customer path has an indirect effect only, fully mediated by firms’ relational performance. Customer tenure and customer’s open-mindedness are contingency variables in the digital technology usage – servitization path – firm performance framework. Research limitations/implications A path perspective is useful to conceptualize the servitization processes in manufacturing industries. Future research should investigate the sequential choice of servitization paths and explore its drivers and performance outcomes. Practical implications To create and claim superior value for their customers, managers can choose between two servitization paths, leading to differential performance outcomes. While digital technology usage is key to progress on both paths, it is particularly effective for newly acquired customers on the customer path. Suppliers should target their value-creating service offerings at open-minded customer firms to reap their full performance potential. Originality/value Propose and empirically validate a path-perspective on servitization. Understand the pivotal importance of digital technology usage for both servitization paths.
Keywords: Marketing

Der Hauptschulabschluss als sozial selektiver Hauptzulieferer des Übergangssystems - Sommer, Christian (Berufsbildung. Zeitschrift für Theorie-Praxis-Dialog)
Über zwei Drittel der Anfänger*innen im Übergangssystem verfügen maximal über einen Hauptschul-/Mittelschulabschluss. Sie sind damit überrepräsentiert, was sich weniger durch ihre Kompetenzen als mit ihrem sozioökonomischen Status und klassenspezifischen Nachqualifizierungsverhalten erklären lässt.
Keywords: Social inequality; Transition system

A Regret Policy for the Dynamic Vehicle Routing Problem with Time Windows - Dieter, Peter (Lecture Notes in Computer Science)